The Four Speeches Every Youth Leader Has to Know: The Preaching of Jesus as Model for a Public Rhetoric for Youth Ministry - Norheim, Bård (Journal of youth and theology, 2019)
This article outlines a public rhetoric for youth ministry in an era of ecclesial agoraphobia. The article draws on the findings of a larger research project titled The Four Speeches Every Leader Has to Know. With the use of rhetorical theory, analysis of actual speeches, and a phenomenological and narrative approach to leadership and speaking, this research project has developed a four speeches-typology - the opening speech, the executioner speech, the consolation speech, and the farewell speech. The article uses this typology within the framework of a biblical rhetoric, looking at the speeches of Jesus, to analyse how the four speeches of Jesus may help the youth leader to address the transitory lives of young people in a credible way.